Experimental Analysis of DC Water Pumps with Non-Geared and Geared Mechanism in Air Cooler Prototypes - Sabri, Syahmi Aiman; Mohamad, Khairul Anuar (Evolution in Electrical and Electronic Engineering, 2025)
The paper includes the results of the conducted experiment on DC water pumps performance, which have geared and non-geared mechanisms built into prototypes of air coolers. The research is intended to analyze electrical and thermal performance such as power usage, the stability of current, temperature condition, and efficiency at a specific test condition. A monitoring system was developed with the ESP32 microcontroller using real-time data sensors and uploaded in Google sheets through Wi-Fi. Experimental results showed that non-geared pumps achieved an average efficiency between 80–85% with lower current usage (0.36–0.38 A) and more stable temperature (21.81–26.50 °C), while geared pumps showed lower efficiency (70–75%) and higher current draw (0.41–0.46 A). This suggests non-geared pumps are more suitable for energy-limited or tropical locations in sustainable air-cooling systems.